North Atlantic Micro State Security Governance: Facing Structural, Natural and Political Challenges Historically, Today and in the Future - Bertelsen, Rasmus (2011)
Rasmus Bertelsen, United Nations University Institute of Advanced Studies, Japan, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.